Topics in National Anthems - Radu Silaghi-Dumitrescu (Journal of Language and Literature, 2020)
National anthems are occasionally quoted, mostly based on anecdotal evidence or arguments, to be correlated with societal features. The present study aims to identify the pervasive topics in national anthems, and then to establish whether connections may be established between these topics and some basic societal features. Upon examination of ~200 anthems, such recurring themes were identified: ancestry/past, beauty, build/work, country name, courage, democracy, enemy, ethnicity, family, man, woman, fight, flag/colours, forever/never, future, geographical references, glory, independence/freedom, joy/happiness, home/mother/father-land, law/governance, leader, love, loyalty, peace, poverty/wealth, pride, religion, revolution, sacred, sacrifice, salvation, sorrow, treason, tyrant/chains, unity, win/victory. The number of topics, as well as their bias (e.g., towards identity, or towards fight, or towards general well-being), vary widely between anthems; groups of anthems may be identified based on these tendencies. Moreover, the number of topics, their bias, and/or the date of adoption can be proven to correlate to some extent to more general societal features such as date of adoption, age of country, gross domestic product (GDP) per capita, Gini coefficient, size of armed forces, inequality, inequality-adjusted human development index, and a number of parameters from the World Values Survey (WVS) database (related to religion, gender equality, attitude towards other nationalities/races, attitude towards work, attachment to democratic values etc). This set of data and the herein identified correlations may offer grounds for further, more detailed exploration of a variety of correlations between societal features and official narratives, starting with the national anthems as prime example.